Limiting Factors of Foreign Direct Investment Undertaken By Polish Enterprises. Issue 3 (3rd July 2019) - Jaworek, Małgorzata; Szałucka, Małgorzata; Karaszewski, Włodzimierz
Abstract: Limiting factors of foreign direct investment are of great significance for managers, governments, and scholars as they directly influence the profitability of a foreign subsidiary and a parent multinational company. The aim of the paper is to identify FDI limiting factors of host country location choices among Polish enterprises and differences in the perception of the factors depending on the establishment mode choice, i.e. whether it is through greenfield investments or acquisitions. The paper presents results of a field surveyed carried out in 2012–2013 among Polish companies. The research results revealed that regardless of the establishment mode choice, investors from Poland perceived market-related limiting factors as significant. The empirical findings also proved that there were no significant differences in the perception of the importance of FDI limiting factors, between investors who undertook acquisitions and those who decided to make greenfield investments. However, single cases of differences were identified at the level of the policy framework-related factors.